Bloodstream infections in pediatric hematology/oncology patients: a single-center study in Wuhan - Murshed, Ibrahim Ahmed Saleh; Zhao, Lizhen; Zhang, Wenzhi; Yin, Yuhong; Li, Ying; Peng, Yun; Chen, Hongbo; Wu, Xiaoyan (Frontiers in Cellular and Infection Microbiology, 2024)
Bloodstream infections (BSIs) are a critical concern in pediatric onco-hematological patients undergoing chemotherapy or hematopoietic stem cell transplantation (HSCT), leading to a major impact on morbidity, long-term hospitalization, and mortality. We retrospectively analyzed 202 BSIs in 145 patients, consisting of 128 with hematological malignancies, one with a solid tumor, and 16 with non-malignant hematological diseases. We collected data on patient demographics, clinical characteristics, pathogen distribution, and antimicrobial pathogen susceptibility. Gram-positive infections were the most frequent at (58.4%), followed by gram-negative (41%), and fungal infections (0.5%). Particularly, the majority of these infections occurred during the induction phase of chemotherapy, where 94 (46.5%) BSI episodes were recorded, predominantly in neutropenic patients (88.3%). The consolidation phase experienced lower BSIs (11.8%); among these patients (54.1%) were non-neutropenic. BSIs observed in (23.7%) of patients in the maintenance phase, with a higher proportion (66.6%) being neutropenic. Among the 7 patients who underwent HSCT, BSIs occurred in (4.9%) cases, mainly (70%) due to neutropenia. The most prevalent pathogens were Staphylococcus epidermidis (19.8%), Staphylococcus hominis (16.3%), and Escherichia coli (8.4%). The study highlights the critical need for vigilant monitoring and customized infection management strategies to enhance patient outcomes across chemotherapy phases and HSCT.